THE EFFECTS OF COMPUTER-ASSISTED LEARNING ON THE ACHIEVEMENT AND PROBLEM SOLVING SKILLS OF THE EDUCATIONAL STATISTICS STUDENTS - Tareef, Atif Bin (European Scientific Journal, ESJ, 2014)
The basic aimed of this study is to investigate the effects of Computer Assisted Learning on the achievements of the educational statistic students the measurements related to the experimental and control groups. The result showed that, the difference is on behalf of the experiment group. This fact shows that the Computer-assisted learning method and traditional education methods have a clear different effect on the student’s educational statistics achievements. This result leads that experiment group’s students with computer-assisted learning methods increase their achievement level and show a higher performance more than the control group students.